Publishing Online for Writers - Kesteven, Lisa. author. aut Link
XIII, 204 p. 13 illus., 7 illus. in color.
Keywords: Publishing online can be a daunting prospect for any writer. This book equips aspiring writers with a range of practical skills and tactics for entering the online publishing world. It will guide readers on where and how to publish online, whether writing for magazines, journals, blogs, or podcasts. The textbook includes practical exercises for developing skills such as producing an e-book, creating an e-book marketing strategy, and building an online writer’s presence. It also features step-by-step guides, examples and checklists that help readers research and find appropriate sites to submit work to, and show how to take a completed manuscript through to publication. This textbook will appeal to students, freelance writers, creative writers, poets, novelists and anyone interested in publishing content online to promote and sell their work more effectively. .